The Impact of Public Relation on Company Effectiveness at Pt. Global Aksara Motor Medan - Javerson Simamora; Edward Harnjo; Eddy Gunawan; Erni Dewi Munte; Mega Sanjaya (Universitas Muhammadiyah Palu, 2025)
Public relations as the management of communication between an organization and it publics. Public relations encompass the overall planning, execution, and evaluation of an organization’s communication with both external and internal publics. The goal of public relations is to help an organization to increase the company effectiveness. Getting a clear understanding of an organization’s business goals is the first step of public relations activities to set measurable objectives for a communication program. Company effectiveness is the company success by a few short term measures in sales and profit and long term perspective such as combining short term with customer service goals.The director of PT. Global Aksara Motor Medan concluded that the marketing manager does not take part in setting company’s objectives, low level of expertise for conducting public relations research and lack of budget dedicated to public relations.the problem identifications of the company is Is there impact of public relation on company effectiveness and How strong is the impact of public relation on company effectiveness. The population of PT. Global Aksara Motor Medan is the employees of marketing department. The writer uses Arikunto sampling theory. The sample size is 45. The writer uses census sampling technique which the writer takes all population as sample. In analyzing data, the writer used some methods such as data descriptive, the validity test, the reliability test, the correlation test, the determination test,linier regression, and the hypothesis test. According to the result calculation data through the answers of the respondents, the writer got the result of 0.72 means Public relation has a strong impact on company effectiveness at PT. Global Aksara Motor Medan. From the calculation of ztest hypothesis test, the writer got zcount=4.77. The zcount > ztable (4.77> 1.96), This means the Null hypothesis (Ho) is rejected. The writer can conclude that public relation has impact on company effectiveness at PT. Global Aksara Motor Medan.